صراع النخب وأثره على السياسة التربوية في الجزائر - ريابي, محمد; درويش, جمال (University of Eloued جامعة الوادي, 2021)
تلقى السياسات التربوية مكانة بارزة في أجندة صانعي القرار، على افتراض أنها وسيلة لتحقيق التطور، ولكنها في نفس الوقت أداة فعالة في يد النظام السياسي للحفاظ على استقراره، ونظرا لأهمية هذا القطاع بالنسبة للفواعل المؤثرة في السياسة العامة بصفة خاصة والمجتمع عامة، فقد عرفت الجزائر عدة إصلاحات في منظومتها التربوية، تميزت بسجال فكري وصراع إيديولوجي بين التيار الفرانكوفوني وأخر الوطني العروبي. حيث سنتناول في هذه الدراسة دور النخب في صنع السياسة التربوية في الجزائر، من خلال التركيز على الطرح المتباين لفريق يناظر لربط المناهج التعليمية بالموروث الحضاري والثقافي الجزائري ونقيضه تغريبي يسعى إلى وصل المدرسة الجزائرية بالقيم الفرنسية وحضارتها وثقافتها. Educational policie takes a large place in the agenda of decision-makers. It’s a mean of achieving development, But at the same time, it is an effective tool in the hands of the political system to maintain its stability. Given the importance of educational sector to influence actors in public politics as well as in society as a whole. Algeria has known several reforms that have affected the educational system, characterized by an intellectual and ideological conflict between the Francophone current and the national Arab trend. In this study, we will study the role of elites in making educational policies in Algeria by focusing on two different propositions, the first defending linking educational curricula with the Algerian cultural and historical heritage, and the second defending the need to modernize the school and open up more to Western values and culture, especially the French one.
مجلد12، عدد1
Keywords: السياسة التربوية ; النخبة ; المناهج التعليمية ; الصراع الايديولوجي ; المدرسة; Educational policy; Elite; Educational curricula; Ideological struggle; School.